PERGESERAN PARADIGMA PADA LAYANAN PERIJINAN MELALUI NEW MODEL SERVICE BERBASIS CITIZEN CENTRIC - Dwi Suharnoko; Umi Chayatin; Chandra Dinata (Social and Political Science Faculty - Universitas Tidar, 2018)
An important point in good governance is essentially the provision of excellent service to people who have citizenship rights that must be provided by the government. Globalization has encouraged paradigm changes in government in carrying out its distributive function to the community. As much as developed countries have done, public encouragement accompanied by public participation in all governance processes leads the country to